High temperature corrosion of nanocrystalline three-phase Cu-20Ag-20Cr bulk alloy. (September 2016) - Cao, Z.Q.; Li, C.W.; Jia, Z.Q.; Wang, Y.
Graphical abstract: Highlights: When grain size is refined, the corrosion rates of Cu-20Ag-20Cr alloy become higher at 600–700 °C, but lower at 800 °C. Coarse-grained Cu-20Ag-20Cr alloy is unable to form the scales of chromia. Nanocrystalline Cu-20Ag-20Cr alloy is also unable to form the scales of chromia at 600 °C. Nanocrystalline Cu-20Ag-20Cr alloy is able to form a bright and continuous layer of Ag2 O at 700 °C. Nanocrystalline Cu-20Ag-20Cr alloy is able to form an irregular and continuous layer of chromia at 800 °C. Abstract: High temperature corrosion of nanocrystalline MACu-20Ag-20Cr(at.%) alloy prepared by mechanical alloying(MA) was studied as compared with that of coarse grained PMCu-20Ag-20Cr alloy prepared by powder metallurgy(PM). PMCu-20Ag-20Cr alloy forms an external layer composed of CuO or CuO and CuCr2 O4, while the internal layer is composed of alloys as well as Cu, Ag and Cr oxides. MACu-20Ag-20Cr alloy forms the same scale structures as PMCu-20Ag-20Cr alloy at 600 °C. On the contrary, it forms a bright layer of Ag2 O at 700 °C, but an irregular and continuous layer of chromia at 800 °C, which prevent the alloy from being oxidized further.